Application of Nanoparticles in the Treatment of Lung Cancer With Emphasis on Receptors - Wang, Jingyue; Zhou, Tong; Liu, Ying; Chen, Shuangmin; Yu, Zhenxiang (Frontiers in Pharmacology, 2022)
Lung cancer is one of the malignant tumors that has seen the most rapid growth in terms of morbidity and mortality in recent years, posing the biggest threat to people's health and lives. In recent years, the nano-drug loading system has made significant progress in the detection, diagnosis, and treatment of lung cancer. Nanomaterials are used to specifically target tumor tissue to minimize therapeutic adverse effects and increase bioavailability. It is achieved primarily through two mechanisms: passive targeting, which entails the use of enhanced penetration and retention (EPR) effect, and active targeting, which entails the loading recognition ligands for tumor marker molecules onto nanomaterials. However, it has been demonstrated that the EPR effect is effective in rodents but not in humans. Taking this into consideration, researchers paid significant attention to the active targeting nano-drug loading system. Additionally, it has been demonstrated to have a higher affinity and specificity for tumor cells. In this review, it describes the development of research into active targeted nano-drug delivery systems for lung cancer treatment from the receptors' or targets’ perspective. We anticipate that this study will help biomedical researchers use nanoparticles (NPs) to treat lung cancer by providing more and novel drug delivery strategies or solid ligands.